2017
DOI: 10.1111/fme.12243
|View full text |Cite
|
Sign up to set email alerts
|

Age‐0 blue catfish habitat use and population demographics in the middle Mississippi River

Abstract: The demographics (e.g. hatch time, growth and mortality) and habitat (macrohabitat and mesohabitat) use of age‐0 blue catfish Ictalurus furcatus (Lesueur) were evaluated in the un‐impounded reach of the middle Mississippi River during 2003–2010. Each year, island complexes and adjacent main river habitats were trawled, and 7,373 age‐0 blue catfish (10–144 mm total length) were collected. Blue catfish hatch timing varied slightly across years and generally began in June and ended in August. Age‐0 blue catfish g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In addition to distance to the river mouth (rkm) and relative distance to upstream and downstream dams, islands also had a strong influence on fish assemblages. My results, consistent with previous studies, suggest that habitats around islands provide unique functional process zones (i.e., areas of unique hydro and fluvial geomorphic characteristics) that promote habitat heterogeneity (i.e., variations in depth, flow, substrate, and vegetation) necessary for the life history of certain fishes (i.e., Paddlefish, Sturgeon, Darters, Catfishes, and others) (Freedman et al 2010;Freedman et al 2014;Haupt and Phelps 2016;Love et al 2017;Seibert et al 2017). All percid species (i.e., darters) that were collected in adequate frequencies (e.g., ≥ 10% of all samples) were associated with islands in terms of their greatest relative abundance, suggesting that island areas should be of conservation focus.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to distance to the river mouth (rkm) and relative distance to upstream and downstream dams, islands also had a strong influence on fish assemblages. My results, consistent with previous studies, suggest that habitats around islands provide unique functional process zones (i.e., areas of unique hydro and fluvial geomorphic characteristics) that promote habitat heterogeneity (i.e., variations in depth, flow, substrate, and vegetation) necessary for the life history of certain fishes (i.e., Paddlefish, Sturgeon, Darters, Catfishes, and others) (Freedman et al 2010;Freedman et al 2014;Haupt and Phelps 2016;Love et al 2017;Seibert et al 2017). All percid species (i.e., darters) that were collected in adequate frequencies (e.g., ≥ 10% of all samples) were associated with islands in terms of their greatest relative abundance, suggesting that island areas should be of conservation focus.…”
Section: Discussionsupporting
confidence: 79%
“…This is the first evidence of Blue Catfish reproduction in West Virginia waters. However, additional monitoring, fecundity, and more extensive population assessments of this species are needed to confirm if this population is naturally viable (Slipke et al 2004;Love et al 2017;Seibert et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Moody-Carpenter et al (2017) reported no measure of uncertainty around the modeled F, and modeled values for the lower Ohio River were not statistically different from zero. Although differences in gears and catchabilities cannot be excluded as potential explanations for the differences in A, the high value of F (combined exploitation by anglers and commercial fishers) in the Wabash River is a plausible explanation for our observed differences in A. Alternatively, A can be influenced by an array of biotic and abiotic factors (Allen et al 2008;Horppila et al 2010;Forsythe et al 2012;Seibert et al 2017) and inherent differences between river systems or populations.…”
Section: S372mentioning
confidence: 87%
“…In their native range, Blue Catfish spawn from April to August (Graham ; Seibert et al. ), and peak spawning occurs during May and June in the Chesapeake Bay region (V. Nepal, unpublished). Age‐0 fish may not fully recruit to our sampling gear until September.…”
Section: Methodsmentioning
confidence: 99%